Notary Protection of Authentic Deeds as Evidence in Criminal Cases - Santoso, Irwan; Prayitno, Ahmad Hadi (TABELLIUS: Journal of Law, 2025)
Abstract. The purpose of this study is to determine and analyze the implementation of notarial protection for authentic deeds as evidence in criminal cases, to determine and analyze the obstacles and solutions to the implementation of notarial protection for authentic deeds as evidence in criminal cases. The research method used in this thesis is the sociological legal method. The results of the study indicate that: Obstacles to legal protection for notaries as public officials if indicated in a criminal case, which is regulated in this Law. Authentic deeds that must still be made and stored conventionally. Currently there are no regulations regarding the clarity of notarial actions that can be categorized as unlawful acts when carrying out their duties and responsibilities. The legal protection for notaries when carrying out their duties and responsibilities is not yet clear. There is no legal certainty that there are limitations in filing lawsuits by the parties when a violation of the law occurs by a notary, which of course must first be based on the results of the examination and determination of the Regional Supervisor/Regional Supervisor regarding the truth of the violation of the Notary Code of Ethics when carrying out their duties and responsibilities. Thus, a solution was drawn to overcome this, namely creating a mechanism regarding the obligation to provide evidence by the Notary Supervisor at the regional level so that the determination of the MPN becomes the basis for the parties to be able to file civil or criminal lawsuits.Keywords: Authentic Deed; Criminal Case; Legal Protection; Notary.